Social Media as an Effective Marketing Tool : An Empirical Study - Shimpi, Siddharth Shriram (Indian Journal of Marketing, 2018)
Social media has introduced a unique aspect to marketing strategy, where once companies dictated what was said about their brands to a passive audience, consumers have now become the creators and distributors of these messages. Designing communication for social media is a different ball game with increasing awareness and impatient audience, rising competition, and cost. Management education in India has lately turned into more of a business than an attempt to educate the people of the county. This field has felt a dire need of most effective promotional media. Besides conventional forms of promotion, social media can be one of the tools which can keep the institutions in limelight. The existing empirical study was directed to focus on social media as an effective marketing tool for management institutes in Pune city. A structured and undisguised questionnaire was developed and was used to collect primary data from 566 respondents. A conceptual model was investigated by using structural equation modeling and the impact of external constructs on the internal construct was tested. This study provided detailed insights on various elements used for analysis and revealed that electronic word-of-mouth and social image influenced impression management, which in-turn influenced opportunities of branding through social media. Furthermore, this study confirmed the mediating role of impression management in electronic word-of-mouth and social image on branding of management institutes.